The rise of liberalism and religious pluralism in Malaysia - Jamaludin, Najiah Athirah; Ibrahim, Haslina (IIUM Press, 2017)
Among the widely spread and controversial philosophies that are receiving global attention today are the philosophy of liberalism and religious pluralism. Having its origin in the Western bedrock, both philosophies are products of modernity in the series of struggle against religion and tradition. Malaysia, without exception has long been exposed to both philosophies. Since the beginning of this century, there has been visible support for both philosophies from certain groups which has led to public and intellectual debates. This work, therefore, seeks to explore the narrative of liberalism and religious pluralism in Malaysia and to explain both the meaning and the relationship to objectively analyse their challenges to Muslim faith in Malaysia. Therefore, the challenges deliberated in this work spans from the question of human rights and freedom, which include the problem of apostasy and conversion among the Muslims, and the liberal values and norms propagated by LGBT groups in Malaysia. This work is theoretical and philosophical, and therefore, is qualitative in nature and depends much on textual research. The resources include printed and online materials. To analyse the data, the author has adopted critical and analytical methods. The findings show that acceptance of liberalism and religious pluralism by Muslims is the result of confusion and misinterpretation of texts on the origin, context and the challenges brought by these philosophies to religion in particular to Islam, being the religion of the nation. The work therefore commends that genuine understanding on both philosophies are crucial before any support or rejection can be made. In addition, much has been written on both philosophies but there is little research done on the relationship between them. This work, therefore, fills this gap.